Harnessing technologies for sustainable development in Africa. Fifth annual Peter Doherty Distinguished Lecture - Amoako, K.Y. (International Livestock Research Institute, 2003)
During this lecture, the Peter Doherty Distinguished Lecturer Mr. Amoako, tried to convey his idea of sustainable development and why it has declined in Africa over the last 30 years. He argues that sustainability is a direct function of institutional development, human and physical capital accumulation as well as productivity. He indicates a few of the most critical challenges Africa must address to achieve sustainable development and a better life for its citizens. Then suggests how new technologies can help respond to these challenges. The concept of sustainable development was described from the point of vantage of the lecturer as “Sustainable development is easy to explain but substantially more difficult to realise. Basically, it is development that meets the needs of the present without compromising the ability of future generations to meet their own needs. It is a pattern of development that ensures a steady enhancement of well-being over time. It requires structural changes that lead to enduring widespread improvements in the quality of life of a society. Sustainable development requires a systematic, carefully co-ordinated, and interconnected series of policies and strategies that will improve people's lives in a progressive, irreversible and palpable manner”. The author indicates that the most fundamental development challenge in Africa today is poverty reduction. The stark reality is that Africa is not even able to feed itself and must rely on 3.23 million tonnes of food aid annually to stave off starvation. The key to reversing this trend is agriculture; that Africa must fight poverty through an agricultural revolution. The lecturer indicates that the fact is we know what we need to achieve the goal of sustainable development. But it will not be easy. He identifies six critical challenges which we must address and cure if we are to have a chance at success. These six issues are discussed widely in this report, and these are - Africa's development; sustainable development; poverty reduction; health factor; food security, gender dimension/human capital; and ICT - information and communication technology.